(untitled) - Roberts, Ian G. (Cambridge, 2003)
This book shows how this approach leads to a number of important conceptual and theoretical issues concerning the nature of functional categories and the form of parameters, as well as the relation of both of these to language change.
Keywords: Grammar, comparative and general,Linguistic change,Minimalist theory (Linguistics),Tổng quan về cú và phép so sánh; Grammaticalization,Ngữ pháp học